2021
DOI: 10.3892/etm.2021.9987
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNA, lncRNA and circRNA in the development of intervertebral disk degeneration (Review)

Abstract: Intervertebral disc degeneration (IVDD) is a degenerative musculoskeletal disorder with multiple causative factors, such as age, genetics, mechanics and life style. IVDD contributes to non-specific lower back pain (NLBP), which is a globally prevalent and debilitating musculoskeletal disorder. NLBP has a substantial impact on medical resources and creates an economic burden for the public. Dysregulated phenotypes of nucleus pulposus (NP) cells and endplate chondrocytes, such as proliferation, senescence and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…The competing endogenous RNA (ceRNA) hypothesis is an important mechanism that allows circRNAs in cancers by sponging microRNAs (miRNAs) to modulate mRNAs [ 24 ]. Increasing evidence shows that the circRNA and miRNA can regulate apoptosis and autophagy of cells [ 7 , 25 , 26 ], including NP cells [ 27 ]. These identified ceRNA interaction aces may be crucial targets for treatment of IDD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The competing endogenous RNA (ceRNA) hypothesis is an important mechanism that allows circRNAs in cancers by sponging microRNAs (miRNAs) to modulate mRNAs [ 24 ]. Increasing evidence shows that the circRNA and miRNA can regulate apoptosis and autophagy of cells [ 7 , 25 , 26 ], including NP cells [ 27 ]. These identified ceRNA interaction aces may be crucial targets for treatment of IDD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs act as competing endogenous RNAs to sponge miRNAs, and to subsequently regulate the expression of target genes ( 28 , 56 , 61 , 62 ). As Ma et al ( 8 ) reported, circ-UBAP2 knockdown inhibited the progression of OS cells by upregulating the expression of miR-204-3p and, thus, downregulating the expression of its target gene, HMGA2.…”
Section: Discussionmentioning
confidence: 99%
“…miR-141-3p functions as a tumor suppressor in OS, colorectal cancer and gastric cancer (24)(25)(26)(27). Additionally, in recent years, a number of studies have demonstrated that circRNAs can competitively bind to miRNAs, thereby eliminating the regulatory effect of miRNAs on their target genes and participating in tumor progression (28,29). For instance, in non-small cell lung carcinoma (NSCLC), circ_100395 inhibited NSCLC malignancy by sponging miR-141-3p and thereby increasing the expression levels of large tumor suppressor kinase 2 (30).…”
Section: Circ-lrp6 Contributes To Osteosarcoma Progression By Regulat...mentioning
confidence: 99%
“…The dysregulation of lncRNA expression influences apoptosis of disk cells, implying relevance in the development of intervertebral disk degeneration (IDD) 68,69 . OIP5‐AS1 has specifically been implicated in IDD where it has been found in a ceRNA network (along with KCNQ10T1 and UGDH‐AS1) to regulate hsa‐miR‐140, which is involved in cartilage development and osteoarthritis pathogenesis 70 .…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%